2018
DOI: 10.1111/josh.12626
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Organizational Culture on School‐Based Obesity Prevention Interventions: A Systematic Review of the Literature

Abstract: Organizational culture can greatly influence the success of school-based obesity interventions. The collection of data related to organizational-level factors may be used to identify strategies for creating and sustaining a supportive environment for obesity prevention interventions in the school setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
(122 reference statements)
1
5
0
Order By: Relevance
“…Using latent profile analysis, the researchers analyzed the cultures and climates of 65 schools and found that 9% of the schools exhibited a comprehensive culture and climate profile in which proficient culture was high, rigid and resistant culture were moderate to low, functional and engaged climate were high, and stressful climate was low—fidelity to EBPs for youth with autism was significantly higher in these schools (Williams et al, 2019). These findings extend a substantial body of school-based research showing that school cultures and climates predict student achievement, social-emotional well-being and behavior, and staff retention and burnout (Anderson, 1982; Fair et al, 2018; Hargreaves, 2013; Hoy, 1990; Huang et al, 2017; Kohl et al, 2013; Macneil et al, 2009; Reaves et al, 2018; Thapa et al, 2013). These findings also beg the question: what can school leaders do to create comprehensive cultures and climates that support EBP implementation for youth with autism?…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Using latent profile analysis, the researchers analyzed the cultures and climates of 65 schools and found that 9% of the schools exhibited a comprehensive culture and climate profile in which proficient culture was high, rigid and resistant culture were moderate to low, functional and engaged climate were high, and stressful climate was low—fidelity to EBPs for youth with autism was significantly higher in these schools (Williams et al, 2019). These findings extend a substantial body of school-based research showing that school cultures and climates predict student achievement, social-emotional well-being and behavior, and staff retention and burnout (Anderson, 1982; Fair et al, 2018; Hargreaves, 2013; Hoy, 1990; Huang et al, 2017; Kohl et al, 2013; Macneil et al, 2009; Reaves et al, 2018; Thapa et al, 2013). These findings also beg the question: what can school leaders do to create comprehensive cultures and climates that support EBP implementation for youth with autism?…”
Section: Introductionsupporting
confidence: 78%
“…One factor that predicts effective EBP implementation in schools is the school’s organizational culture and climate (Fair et al, 2018; Williams et al, 2019), where culture is defined as the shared norms and behavioral expectations that guide how work is completed within the organization (Glisson, Landsverk, et al, 2008) and climate is defined as employees’ shared perceptions of the impact of the work environment on their personal well-being (James et al, 2008). Several studies have drawn on a theoretical model that defines organizational culture along three dimensions of proficiency, rigidity, and resistance, and organizational climate along three dimensions of engagement, functionality, and stress (Glisson, Landsverk, et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It should be, however, noted that teachers alone cannot solve the weight discrimination. Fostering a positive and supportive school climate, for instance, may also help obese children to avoid weight discrimination/stigmatization (Winter, 2009;Fair et al, 2018). More importantly, since major risk factors for child obesity lie outside of schools (Von Hippel and Workman, 2016), careful monitoring of children with earlyonset obesity should also take place within families and schools with obesity intervention programs [see also Bleich et al (2017), Jakicic and Davis (2011)].…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Responses from school administration participating in the COMPASS study contribute to the reality that schools encounter a number of barriers in their efforts to improve student health. The most referenced barriers to health program implementation included “inadequate staff time available to implement programs” and “inadequate funding and support for school‐based health programs and services for students.” The presence of barriers to implementing health programs and policies in schools are not uncommon in the literature 35,36 . Disconnection with school staff members, inability to establish connections with external partners, a lack of time due to increasing workload, lack of available resources and lack of funding were shown to hinder the success of policy implementation in some Canadian schools 36,37 .…”
Section: Discussionmentioning
confidence: 99%